SHARP CONSTANTS IN THE POINCARÉ, STEKLOV AND RELATED INEQUALITIES (A SURVEY). Issue 2 (10th October 2014) - Kuznetsov, Nikolay; Nazarov, Alexander
Abstract : During the past 55 years substantial progress concerning sharp constants in Poincaré‐type and Steklov‐type inequalities has been achieved. Original results of H. Poincaré, V. A. Steklov and his disciples are reviewed along with the main further developments in this area.